Can Business Input Improve the Effectiveness of Worker Training? : Evidence from Brazil's Pronatec-MDIC - O'Connell, Stephen D.; Mation, Lucas Ferreira; Bevilaqua T. Basto, Joao; Dutz, Mark A. (World Bank, Washington, DC, 2017)
This study evaluates the employment effects of a publicly-run national technical vocational education training program in Brazil that explicitly takes input from firms in determining the location, scale, and skill content of courses offered. Using exogenous course capacity restrictions, the study finds that those completing the course following receipt of a course offer have an 8.6 percent increase in employment over the year following course completion. These effects come from previously unemployed trainees who find employment at non-requesting firms. The demand-driven program's effects are larger and statistically distinguishable from those of a broader and institutionally-similar publicly-administered skills training program run at the same time that did not take input from firms. The study finds that the demand-driven program better aligned skill training with future aggregate occupational employment growth -- suggesting the input from firms captured meaningful information about growth in skill demand. Courses offered in occupations that grew more over the year following requests exhibited larger employment effects, explaining the effectiveness of the demand-driven model.